Automata-based Symmetric-key Cryptosystems - Skeen, Luke (My University, 2021)
Three symmetric-key cryptosystems based on different types of finite automata are studied in this thesis. One is a block cipher based on extended Mealy machines (a type of automaton with output) which was invented by Marc Gysin in 1995. The other two are block ciphers which were invented by Pál Dömösi and Géza Horváth in 2015: both are based on semiautomata (a type of automaton without initial and final states); however, one of them uses Gluškov products (a type of semiautomaton whose components are other, interconnected semiautomata).
Keywords: symmetric-key cryptography, finite automata, semiautomata, Mealy machine, extended Mealy machine